Comparative safety and effectiveness of inhaled bronchodilators and corticosteroids for treating asthma–COPD overlap: a systematic review and meta-analysis. (4th March 2021) - Amegadzie, Joseph Emil; Gorgui, Jessica; Acheampong, Lily; Gamble, John-Michael; Farrell, Jamie; Gao, Zhiwei
Abstract: Objective: To determine the safety and effectiveness of current pharmacotherapies consisting of long-acting beta2 -agonist (LABA) and/or inhaled corticosteroids (ICS) in patients with asthma–COPD overlap. Data sources: A systematic search was conducted using the PubMed, EMBASE, and Web of Science databases up to June 2018. Study selections: Only studies comparing the safety and effectiveness of LABA and/or ICS in patients with asthma–COPD overlap were included. A meta-analysis was performed to calculate risk ratio (RR) and 95% confidence interval (CI) using Inverse Variance Random-effects model. Results: From a total of 3382 articles retrieved, three randomized controlled trials (RCTs), six cohort studies (CS), one nested case control study fulfilled the inclusion criteria for three independent meta-analyses representing 181, 603 participants. Three CS results show LABA was associated with decreased risk of myocardial infarction (combined RR: 0.80, 95% CI 0.74–0.87) versus non-LABA use; ICS/LABA was associated with a lower risk of death or hospitalization (combined RR: 0.82, 95% CI 0.75–0.90) compared to no use. Results from RCTs, no clear difference in lung function decline in FEV1 was found (combined mean difference: 0.08, 95% CI 0.15–0.32) in patients receiving ICS and/or LABA compared to placebo. However, due to lack of data, exacerbations, fractures and nontuberculous mycobacterial pulmonary disease outcomes were not meta-analyzed. Conclusions: Among patients with asthma–COPD overlap, LABA is associated with decreased risk of myocardial infarction; and the combination therapy of ICS/LABA appears to reduce the risk of death or hospitalization. More studies of quality data and larger number of patients are needed. REGISTRATION: PROSPERO (CRD42018090863).